Assessing European firms' exports and productivity distributions: The CompNet trade module - Antoine Berthou; Emmanuel Dhyne; Matteo Bugamelli; Ana-Maria Cazacu; Calin-Vlad Demian; Peter Harasztosi; Tibor Lalinsky; Jaanika Meriküll; Filippo Oropallo; Ana Cristina Soares (National Bank of Belgium, 2015)
This paper provides a new cross-country evaluation of competitiveness, focusing on the linkages between productivity and export performance among European economies. We use the information compiled in the Trade module of CompNet to establish new stylized facts regarding the joint distributions of the firm-level exports performance and productivity in a panel of 15 countries, 23 manufacturing sectors during the 2000's. We confirm that exporters are more productive than nonexporters. However, this productivity premium is rising with the export experience of firms, with permanent exporters being much more productive than starters. At the intensive margin, we show that both the level and the growth of firm-level exports rise with firm productivity, and that the bulk of aggregate exports in each country are made by a small number of highly productive firms. Finally, we show that during the crisis, the growth of exports by high productive firms sustained the current account adjustment of European “stressed” economies. This last result confirms that the shape of the productivity distribution within each country can have important consequences from the point of view of the dynamics of aggregate trade patterns.
Keywords: F10; F14; 330; Firm-level exports; productivity; firm heterogeneity; Unternehmen; Industrie; Export; Wettbewerb; Internationaler Wettbewerb; Vergleich; Schätzung; Europa